A New Sutureless Illuminated Macular Buckle Designed for Myopic Macular Hole Retinal Detachment - Ahmed M. Bedda; Ahmed M. Abdel Hadi; Mohamed Lolah; Muhammad S. Abd Al Shafy (Journal of Ophthalmology)
Purpose. To report the anatomic and visual results of a new sutureless illuminated macular buckle designed for patients with macular hole retinal detachment related to high myopia (MMHRD). Design. Prospective nonrandomized comparative interventional trial. Methods. Twenty myopic eyes of 20 patients (mean age, 51.4 years; range, 35–65 years) presenting with MMHRD with a posterior staphyloma, in whom the new buckle was used, were evaluated. The buckle used was assembled from a 5 mm wide sponge and a 7 mm wide silicone tire; it was fixed utilizing the sterile topical adhesive Histoacryl Blue (B Braun, TS1050044FP) which polymerizes in seconds upon being exposed to water-containing substances. The primary outcomes measured included aided visual acuity (BCVA) and optical coherence tomography (OCT) findings. The mean follow-up period was 6 months. Results. Postoperatively, the MH closure was identified by OCT in 8 (40%) eyes. The mean BCVA increased from 0.11 to 0.21 (p<0.005). The axial length of the eyes included decreased from 30.5 mm preoperatively to 29.8 mm (p=0.002) postoperatively. Conclusion. Preparation of the new sutureless macular buckle is simple and easy. Illumination of the terminal part of the buckle ensures proper placement. Histoacryl Blue is effective in fixing the buckle in its place for at least 6 months with no reported intra- or postoperative complications.